War & truth [videorecording (DVD)] - Samstag, Michael (Cinema Libre Sudio, 2007)
War & Truth chronicles the history of embedded journalists from WWII to today. When the United States went to war with Iraq, more than two thousand journalists charged across the Iraqi desert to document history and send the story home. Not everything they saw made it into the newspaper or onto the television news. This film details the courage and frustrations of journalists who risk their lives on the front lines. It dares to bring to light the images you won"t see on the news and explores the true story of what it really means when a nation goes to war.